F-18 FDG PET/CT metabolic tumor volume predicts overall survival in patients with disseminated epithelial ovarian cancer. Issue 93 (August 2017) - Gallicchio, Rosj; Nardelli, Anna; Venetucci, Angela; Capacchione, Daniela; Pelagalli, Alessandra; Sirignano, Cesare; Mainenti, Pierpaolo; Pedicini, Piernicola; Guglielmi, Giuseppe; Storto, Giovanni
Abstract: Objective: We evaluated the prognostic impact of quantitative assessment by maximum standardized uptake value (SUVmax), metabolic tumour volume (MTV) and tumour lesion glycolysis (TLG) on [F-18] FDG PET/CT for patients with peritoneal carcinomatosis from epithelial ovarian cancer (EOC). Methods: Thirty-one patients with EOC underwent PET/CT for an early restaging after cytoreductive surgery, having been diagnosed with carcinomatosis (before chemotherapy). The SUVmax, MTV (cm 3 ; 42% threshold) and TLG (g) were registered on residual peritoneal lesions. The patients were followed up 20 ± 12 months thereafter. The PET/CT results were compared to overall survival (OS). Results: The Kaplan-Meier survival analysis for the SUVmax did not reveal significant differences in OS (p = 0.48). The MTV survival analysis showed a significant higher OS in patients presenting with a higher tumour burden than those with less tumour burden (p = 0.01; 26 vs. 14 months), whereas TLG exhibited a similar trend though not significant (p = 0.06). Apart from chemo-resistance, the higher the MTV, the better will be the response to chemotherapy. Conclusions: Quantitative assessment by MTV rather than by SUVmax and TLG on PET/CT may be helpful for stratifying patients who present with peritoneal carcinomatosis from EOC, in order to implement the appropriate therapeutic regimen.